Reflections on the impact of economic sanctions - Constantinos Syropoulos; Yoto Yotov (EconPol Forum, 2023)
As exemplified by the 2022 and ongoing sanctions on Russia, economic sanctions are more popular than ever in policy circles and an active topic of research. Sanctions aim to achieve political objectives. Nonetheless, despite evidence that their rate of success may be increasing, most sanctions fail to achieve their intended goals. The effects on sanctioned states are strong and adverse. However, the severity of these effects is mitigated by the possible diversion of economic activity toward third countries. Normally, sanctioning states do not suffer large losses. But the sanctions on Russia indicate that these nations may suffer significant losses too. The effects of economic sanctions on third countries, which are transmitted through general equilibrium and extraterritorial channels, may also be extensive and may entail losses or gains.
Keywords: 330